Educational Experiences of Students with Visual Impairments in Higher Education: A Case Study of a Private University - Alghurabi, Ghadeer (AUC Knowledge Fountain, 2024)
The study's main goal is to investigate the educational experiences of students with visual impairments in a private university, considering their views, beliefs, and emotions. The study examines the university's disability policy using Cardno's methodology. Also, The study uses a qualitative research design to learn more about each student's unique experience. Moreover, this study has two components: policy analysis and empirical study (interviews). Policy analysis is used to analyze the disability policy, while student interviews shed insight into their experiences, including the educational challenges they faced, the influence of faculty members, and mobility issues on campus. Furthermore, the Crip theory is used in this study as a theoretical framework. The data collection tools that are used in this study are policy analysis and interviews. Also, both inductive and deductive approaches to coding are used as data analysis tools. The experiences of students at the university are different from one student to another. It has been found that many students with visual impairments are facing a few difficulties, such as mobility, raising awareness, accessible materials, and quality of life, which are mainly because the disability policy is short, broad, and does not indicate many details. This study addresses the shortcomings that are found in the analysis, and the researcher develops a few suggestions depending on the findings.